2009
DOI: 10.1590/s1516-44462009000200008
|View full text |Cite
|
Sign up to set email alerts
|

Highly reported prevalence of drinking and driving in Brazil: data from the first representative household study

Abstract: (OR = 6,0; IC95% 2,(9)(10)(11)(12)6), ter tido acidente prévio com beber e dirigir (OR = 7,9; IC95% 2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)9), ter tido "consumo excessivo episódico" no ultimo ano (OR = 2,2; IC95% 1,(3)(4)5) e ter uma opinião desfavorável sobre políticas públicas (OR = 2,9; IC95% 1,(4)(5)(6)2) 2 Numbers of such magnitude have been repetitive, since policies against drinking and driving have not been regularly enforced. Recently, the government has passed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 20 publications
4
23
0
7
Order By: Relevance
“…3 The first roadside surveys carried out in Brazil have shed light on the wide discrepancies found with regard to the prevalence of drinking and driving (or driving under the influence of alcohol, DUI), ranging from 5 to 40%. [4][5][6][7] Discrepancies notwithstanding, these studies have confirmed international findings highlighting the key role of young, male drivers who consume alcohol in binges as those individuals who are more likely to drive under the influence of alcohol, a behavior that increases the chance of TCs. 8 In an attempt to reduce TCs in Brazil, a new legislation was approved in 2008 (Federal Law 11.705/08, amended December 2012).…”
Section: Introductionsupporting
confidence: 61%
“…3 The first roadside surveys carried out in Brazil have shed light on the wide discrepancies found with regard to the prevalence of drinking and driving (or driving under the influence of alcohol, DUI), ranging from 5 to 40%. [4][5][6][7] Discrepancies notwithstanding, these studies have confirmed international findings highlighting the key role of young, male drivers who consume alcohol in binges as those individuals who are more likely to drive under the influence of alcohol, a behavior that increases the chance of TCs. 8 In an attempt to reduce TCs in Brazil, a new legislation was approved in 2008 (Federal Law 11.705/08, amended December 2012).…”
Section: Introductionsupporting
confidence: 61%
“…The first Brazilian National Alcohol Survey (BNAS) is a nationally representative sample of 3007 Portuguesespeaking household residents in urban and rural areas aged 14 or older (Pechansky et al, 2009). The study was conducted between November 2005 and April 2006.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…Beber e dirigir foi associado com o sexo masculino, com envolvimento prévio em acidentes sob in uência de álcool, uso excessivo de álcool no último ano e opinião desfavorável sobre políticas públicas 8 .…”
Section: Introductionunclassified